2015
DOI: 10.1111/medu.12809
|View full text |Cite
|
Sign up to set email alerts
|

Use of an error‐focused checklist to identify incompetence in lumbar puncture performances

Abstract: ContextChecklists are commonly used in the assessment of procedural competence. However, on most checklists, high scores are often unable to rule out incompetence as the commission of a few serious procedural errors typically results in only a minimal reduction in performance score. We hypothesised that checklists constructed based on procedural errors may be better at identifying incompetence.ObjectivesThis study sought to compare the efficacy of an error-focused checklist and a conventionally constructed che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…A previous study concluded that error‐focused checklists are superior to conventional checklists for determining procedural incompetence . In this study, two types of error metrics, procedural and critical errors were defined.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study concluded that error‐focused checklists are superior to conventional checklists for determining procedural incompetence . In this study, two types of error metrics, procedural and critical errors were defined.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 31 items on the tool, only 16 (52%) were felt to be critically important. Although critical items on clinical and procedural skills have previously been published, 30,[48][49][50][51] to our knowledge, they have not been established for general POCUS skills. Delineating what items are critical is important for POCUS for 2 reasons.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 However, checklists risk ''rewarding thoroughness,'' allowing the successful completion of multiple trivial items while masking the commission of a single serious error. [27][28][29][30][31] As such, there is a need to establish which checklist items are critical in POCUS, such that incompetent performances are appropriately identified.…”
Section: Introductionmentioning
confidence: 99%
“…Improved teaching and learning appears to require simulated practice with part‐task trainers, although this does not necessarily ensure procedural competence . Error‐based checklists have been suggested as a means to assess procedural competence in the simulated setting …”
Section: Discussionmentioning
confidence: 99%
“…9,10 Error-based checklists have been suggested as a means to assess procedural competence in the simulated setting. 11 From the data gathered, paediatricians and paediatric trainees had a greater tendency to perform fundoscopy in infants compared to their emergency counterparts. Brain shifts and ischaemia are the two major consequences of an increase in ICP.…”
Section: Discussionmentioning
confidence: 99%